Sistem Informasi Perencanaan Dan Evaluasi Kegiatan Pembangunan Desa Berbasis Web Pada Desa Huntu Kecamatan Batudaa Kabupaten Gorontalo - Muhammad Yoswandi Marhaba; Lillyan Hadjaratie; Tajuddin Abdillah (Diffusion: Journal of Systems and Information Technology, 2022)
This research is motivated by the obstacles experienced by the village government which has difficulty in delivering information on the results of the village development planning deliberations as well as the Village Revenue and Expenditure Budget (APBDes) to the community, so this makes the lack of transparency from the village government to the community. In addition, there is no system that can process and inform village development planning activities that are ongoing, those that have been achieved and those that have not. The method used in this research is the prototype method. The results of this study obtained the final result in the form of an information system for planning and evaluating village development activities. In addition, with an information system for planning and evaluating village development activities, the system can help the community to get information on planning and evaluating village development activities quickly.